Judicial features of pravozastosuvannya are in a financial right - Касьяненко, Любов Михайлівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
It is marked in the article, that legality is inalienable principle of legitimacy and expedience of pravozastosuvannya.The analysis of judicial norms of financial right allows to classify them on two large groups aftercharacter financially judicial relations which show up depending on a legal fact.